2010
DOI: 10.1016/j.npep.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Y4 receptors and pancreatic polypeptide regulate food intake via hypothalamic orexin and brain-derived neurotropic factor dependent pathways

Abstract: Gut-derived peptides are known to regulate food intake by activating specific receptors in the brain, but the target nuclei and neurons influenced are largely unknown. Here we show that peripherally administered pancreatic polypeptide (PP) stimulates neurons in key nuclei of the hypothalamus critical for appetite and satiety regulation. In the lateral hypothalamic area (LHA), also known as the feeding center, neurons expressing the orexigenic neuropeptide orexin co-localize with the early neuronal activation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Additionally, within the 20 associated regions, we confirmed two previously published obesity associations: CNVR 1p31.1 20 kb upstream of NEGR1 (7,8) and CNVR 10q11.22 (1) covering the four genes SYT15 , GPRIN2 , LOC728643 and PPYR1 (19) with PPYR1 being the most interesting candidate, given its role in energy homeostasis and regulation of food intake (27,32). PPYR1 null animals have, for instance, a reduced body weight.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, within the 20 associated regions, we confirmed two previously published obesity associations: CNVR 1p31.1 20 kb upstream of NEGR1 (7,8) and CNVR 10q11.22 (1) covering the four genes SYT15 , GPRIN2 , LOC728643 and PPYR1 (19) with PPYR1 being the most interesting candidate, given its role in energy homeostasis and regulation of food intake (27,32). PPYR1 null animals have, for instance, a reduced body weight.…”
Section: Discussionsupporting
confidence: 86%
“…PP reduces food intake predominantly via stimulation of the anorexigenic melanocortinergic pathway. This effect is mediated by direct action on local PPYR1 within the arcuate nucleus (32). PP binds to the PPYR1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Y4 receptor is involved in the regulation of feeding [66, 67], circadian ingestion and energy homeostasis [68] and colonic muscle contraction [69]. The human Y4 receptor also plays a critical role in the regulation of food intake and reproductive functions [70].…”
Section: The Characteristics Of Human Npy Receptorsmentioning
confidence: 99%
“…97 Despite its demonstrated anorexigenic effects and its possible anti-obesity utility, the exact hypothalamic nuclei and downstream pathways through which PP Y4 agonism functions to regulate food intake and body weight have, however, yet to be fully elucidated. 99 A recent study in mice has demonstrated the peripheral PP-mediated suppression of orexigenic pathways in the lateral hypothalamic area, or ‘feeding centre', and upregulation of anorexigenic pathways in the ventromedial hypothalamus, or ‘satiety centre'. 99 These effects were shown to be mediated via the Y4 receptor, as they were not reproducible in Y4 receptor knockout mice.…”
Section: Gut Hormones and Obesitymentioning
confidence: 99%